2000
DOI: 10.1038/sj.jhh.1001061
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypertensive status and its drug treatment with lipid and haemostatic factors in middle-aged men: the PRIME Study

Abstract: Aims: To assess the association of hypertensive status and antihypertensive drug treatment with lipid and haemostatic levels in middle-aged men. Methods and results: Hypertensive status, antihypertensive drug treatment, total and high-density lipoprotein (HDL) cholesterol, triglyceride, apoproteins A-I and B, lipoparticles LpA-I, LpE:B and Lp(a), fibrinogen, plasminogen activator inhibitor-1 (PAI-1) activity and factor VII were assessed in a sample of men 50-59 years living in France (n ‫؍‬ 7050) and Northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Some reports have not demonstrated an increase with ACE inhibitors and others have. [39][40][41] Our data corroborate the fact that ACE inhibitors do reduce Lp(a) levels in people with renal insufficiency.…”
Section: Journal Of Human Hypertensionsupporting
confidence: 79%
“…Some reports have not demonstrated an increase with ACE inhibitors and others have. [39][40][41] Our data corroborate the fact that ACE inhibitors do reduce Lp(a) levels in people with renal insufficiency.…”
Section: Journal Of Human Hypertensionsupporting
confidence: 79%
“…Blood pressure reduction with Ca-blockers also improves insulin sensitivi-ty in hypertensive patients (61). On the other hand, many studies have shown that diuretics and β-blockers decrease HDL levels (50,(62)(63)(64) and insulin sensitivity (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…Second, evidence involving the I/D variant of the ACE gene with lipid and lipoprotein levels comes from clinical trials using ACE inhibitors as antihypertensive drug. These drugs have considerable lowering effects, mostly on total and LDL‐C levels (46), and increasing effects on HDL‐C concentrations have also been reported (47). Third, an interaction between ACE I/D polymorphism and plasma lipoprotein/lipid response to fluvastatin (a lipid‐lowering agent) has been reported (7).…”
Section: Discussionmentioning
confidence: 99%